Indoor Localization Estimation Techniques in Wireless Sensor Network: A Review - M. Shahkhir, Mozamir; Rohani, Abu Bakar; Wan Isni Soffiah, Wan Din (IEEE, 2018)
Recently, Wireless Sensor Network (WSN) are an important research area because of its real-time response, accurate, improved node capability, low in cost and simple infrastructure. Because of the huge number of sensor nodes, the main issue of WSN is the estimation of their location. The nodes which are deployed may not be known their own position. In localization, different techniques are used for estimation to gain the coordinate of the node. In this paper, we reviewed on the current techniques in estimation phase for indoor localization from 2013 to 2018. This reviewed will be useful for the researchers to implement the techniques for estimation phase to increase the accuracy.